Isolation and Molecular Identification of Biosurfactant Producing Soil Bacteria - A N Zamani, N; E Tengku Zainal Mulok, T; Mat Nor, R; ., . (International Journal of Engineering and Technology, 2019)
Biosurfactants are amphiphilic compound, having hydrophilic and hydrophobic moieties enabling them to reduce surface and interfacial tension at the surface. Their unique properties are applied in various industries such as foaming and wetting agents, emulsifiers, detergents and bioremediation. A total of 98 isolates showed biosurfactant activity using hemolytic activity, drop collapse test and oil spreading assay. All isolates were rod-shaped, Gram positive and majority of them were non-endospore former. Only the isolates showing the highest percentage of emulsification index (E24) and ability to reduce tension were used for species identification using 16S rDNA gene sequencing which were isolates A1(6) and A2(1). Both isolates were identified as Bacillus sp. cp-h50 and Bacillus sp. XT-24 respectively, rod-shaped, endospore former and Gram positive. The biosurfactant produced by both species showed high emulsification index (E24) (A1(6), 63.3% and A2(1), 46.7%) and good surfactant capacity. The size of amplified gene of 16S rDNA gene was approximately 1.5 kb. These features provide evidence that both species could be a potential biosurfactant producer with proper optimization for the production of biosurfactant. The biosurfactant produced by both bacterial species were identified as surfactin using Fourier Transform Infrared Spectroscopy (FTIR).Â Â